Frequency and Risk Factors of Sleep Problems Among High School Students Who Will Undergo University Entrance Exam as a Stressful Experience - UZUNER, ARZU; ÇİFÇİLİ, SALİHA SERAP (ORTADOGU AD PRES & PUBL CO, 2010)
Objective: Prevalence of sleep disturbances is 15-35%, which is more frequent during adolescence. Stress is known to cause sleep disturbance, in particular insomnia. In this study it is aimed to evaluate the frequency of sleep disturbances among high school students who will undergo a university entrance exam as a stress factor, and relationship of sleep disturbances with the suggested variables. Material and Methods: This descriptive study was conducted in four different types of high schools and a private university preparing exam course in Istanbul. One senior and one junior class from all schools and four classes from the private course were selected by simple randomization and all students were invited to take place in the study. Of the students, 324 accepted to participate and 302 who fully-filled questionnaires were included in the analysis. A self-report questionnaire about main symptoms of sleep disorders and gastro-esophageal reflux, chronic wheezing or cough at nights, coffee and/or tea intake, alcohol and drug use, cigarette smoking, history of chronic diseases and current medications was used to get the data. Chi-square, Student's t-test and binary logistic regression analysis were used. Results: Of the participants, 33.4% (101) reported excessive daytime sleepiness. The participants who reported insomnia were %20.2 (61). The risk factors for insomnia were; addictive drug use, chronic cough and wheezing and depressive symptoms [Odds ratio (OR): 7.33-95% CI: 1.67-32.30, OR: 2.43-95% Cl: 1.31-4.64, 95% OR: 2.10-CI: 1.01-4.10 respectively]. The number of participants who declared that they had sleep disturbances was 121 (40.1%), and 75(24.8%) of the participants reported Obstructive Sleep Apnea (OSA) symptoms. The risk factors for OSA symptoms were; chronic cough and wheezing, gastro-esophageal reflux symptoms and being overweight-obese (OR: 5.07-95% CI: 2.62-9.84, OR: 2.85-95% CI; 1.75-4.67, OR: 95%3.74-CI: 1.75-7.99 respectively). Conclusion: Although sleep difficulties seemed to be very common, this was related to obesity, chronic cough, gastro-esophageal reflux symptoms, cigarette smoking, addictive drug use and depressive symptoms more than exam stress. Thus the students with asthma and those who are overweight may be asked and managed about sleep disorders.
Keywords: Sleep initiation and maintenance disorders; adolescent; stress, physiological; sleep apnea, obstructive; EXCESSIVE DAYTIME SLEEPINESS; PRIMARY-CARE; GENDER-DIFFERENCES; OBESE-PATIENTS; HEALTH-STATUS; ADOLESCENCE; INSOMNIA; DISORDERS; BEHAVIOR; DISTURBANCES